Pengaruh Layanan Konseling Kelompok untuk Menurunkan Perilaku Agresif terhadap Siswa Kelas X SMA Negeri 1 Padang Bolak - Harahap, Dini Anggraini (ANWARUL, 2023)
This research aims to determine the effect of group counseling services to reduce aggressive behavior in class X students at SMA Negeri 1 Padang Bolak. The population used in this research was class X, totaling 264 students. The sample in this research was classes X MIA 1, X MIA 2 and The method used in this research is a quantitative method, namely research that describes the situation regarding the influence between two variables. Data collection techniques in this research used questionnaires, validity tests and reliability tests. Based on the research results, group counseling services have an influence on the aggressive behavior of students at SMA Negeri 1 Padang Bolak with the value of tcount compared to ttable, tcount>ttable (12.366>2.048) with the hypothesis H0 being rejected and Ha being accepted.